Biological science students’ microscopy skills - Teruk, Kamaril Azlah (Center for Foundation Studies, IIUM, 2021)
Fail to get the correct and accurate image of the prepared slide observed under low or high magnification always become the main obstacle for biological science students in doing Biology Laboratory session. Mastery microscope skills not only enable the students to make accurate observation in few experiments of Practical Biology but the skills also significant to be applied for future related sciences subject in Kuliyyah. Through this study, Biological Science student’s microscopy skills and the validity of checklist used in microscopy skill test the has been explored. 22 items (S1-S22) in checklist of Microscopy skill test are groups into 4 themes, pre-observation, manipulation, knowledge, and maintenance give dichotomous score. The data was analysed with SPSS (IBM SPSS version 25) for descriptive analysis. Item statistic, item polarity and item infit was evaluated by Rasch analysis with use Winsteps software (Boone 2017). Descriptive analysis from SPSS have shown no missing values and frequencies for every skill. High frequencies of ‘not score’ or ‘0’ value were shown for skill22 (S22), S15, S16, S17 and S19. Through split case data from SPSS have shown frequencies of ‘not score’ based on students’ programme. Rasch analysis on 22 items of checklist had shown 0.84 items reliability with separation 2.31. From fit analysis, items in the checklist have shown Infit mnsq value between 0.85-1.15 which is within threshold 0.4-1.4 (Kreijns 2020) are conform to the Rasch model (fit to measure 1 construct 1 trait). Items in the checklist had been arranged into series of difficulty level based on value of measure and items with point measure correlation < 0.3 will be further investigate. The outcome of this study has triggers department Biology to make effective modification on biology lab manual on Microscopy 1 to become more understandable in order to assist students learning. Progressive action should be taken to amend specific items in the microscopy checklist as to make the checklist become better summative instrument.